The Influence of Work Discipline and Position Promotion on Employee Performance through Job Satisfaction of LLP-KUKM Jakarta - Nurlaili; Suharto; Saragih, Bongsu (Krisnadwipayana International Journal of Management Studies, 2023)
Every organization aims to have the best performance, therefore, the quality of employees greatly determines the progress of the organization. Employees who are happy with their work routines will be more productive, while those who are dissatisfied with employees will be less productive and are more likely to want to quit their jobs. This study aims to determine the effect of work discipline and job promotion on job satisfaction. It determines the effect of work discipline and job promotion on employee performance. It determines the effect of job satisfaction on employee performance while determining the effect of work discipline on employee performance through job satisfaction and job promotion on performance. LLP-KUKM employees are involved through job satisfaction. The number of samples in this study was 80 employees. The data analysis technique uses path analysis. The results of the analysis show that work discipline and promotion have a significant effect on employee job satisfaction. Work discipline and promotion have a significant effect on employee performance. Job satisfaction has an effect on employee performance. Work discipline affects employee performance through job satisfaction of LLP-KUKM employees. Job promotion has an effect on employee performance through job satisfaction at LLP-KUKM.